2020
DOI: 10.3847/1538-4357/ab8d36
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismic Modeling of Gravity Modes in Slowly Rotating A/F Stars with Radiative Levitation

Abstract: It has been known for several decades that transport of chemical elements is induced by the process of microscopic atomic diffusion. Yet the effect of atomic diffusion, including radiative levitation, has hardly been studied in the context of gravity-mode pulsations of core hydrogen burning stars. In this paper we study the difference in the properties of such modes for models with and without atomic diffusion. We perform asteroseismic modeling of two slowly rotating A-and F-type pulsators, KIC 11145123 ( f ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 70 publications
10
50
0
Order By: Relevance
“…Moving beyond the main sequence, periodic components in the oscillation frequencies due to sharp features in the convective envelope of the red giant HR 7349 were found in its CoRoT data. The signal is due to a local depression of the sound speed in the second ionization zone of helium (Miglio et al, 2010). Similar studies from Kepler observations of red giants were summarized by Hekker and Christensen-Dalsgaard (2017).…”
Section: B Assessing Sharp Features In Stellar Structuresupporting
confidence: 66%
See 1 more Smart Citation
“…Moving beyond the main sequence, periodic components in the oscillation frequencies due to sharp features in the convective envelope of the red giant HR 7349 were found in its CoRoT data. The signal is due to a local depression of the sound speed in the second ionization zone of helium (Miglio et al, 2010). Similar studies from Kepler observations of red giants were summarized by Hekker and Christensen-Dalsgaard (2017).…”
Section: B Assessing Sharp Features In Stellar Structuresupporting
confidence: 66%
“…The capacity of joint asteroseismic aging, sizing, and distance estimation opened up the field of galactic archaeology, which had already been jump-started prior to the Gaia era by Miglio et al (2009). Their study of various populations of core-helium-burning red giants in the galactic disk observed with CoRoT opened a new field of mapping and dating stellar populations from red-giant asteroseismology (Miglio et al, 2013). Meanwhile, extensive progress has been made in archaeological studies for the pointing directions in the Milky Way covered by CoRoT, Kepler, and K2 coupled with large spectroscopic surveys and/ or Gaia data; see Stello et al (2015), Anders et al (2017a), Serenelli et al (2017, Stello et al (2017), Pinsonneault et al (2018), Sahlholdt andSilva Aguirre (2018), Silva Aguirre et al (2018), Rendle et al (2019), Sharma et al (2019), andZinn et al (2019).…”
Section: Applications Of Asteroseismic Modelingmentioning
confidence: 99%
“…Studies of G and F-type stars using grid-based modelling and including acoustic seismic constraints show that atomic diffusion can impact the age of a star by up to 15% (Nsamba et al 2018;Deal et al 2020). Similar results were also found for A-type stars using gravity modes as constraints (Mombarg et al 2020). The effect of rotation is also not taken into account in the models.…”
Section: Masses X C and Ages From Classical Constraintssupporting
confidence: 64%
“…While similar on some fronts, major differences occur in the modelling of g modes compared to the case of stochastically-excited pressure modes (see Aerts 2021, for an extensive review on the overall methodology). For g modes in γ Dor and SPB stars, key processes to infer are convective core overshooting or convective penetration in the core boundary layers (e.g., Pedersen et al 2018;Michielsen et al 2019), interior magnetic fields (Prat et al 2019(Prat et al , 2020Van Beeck et al 2020;Mathis et al 2021, Bugnet et al submitted), and microscopic or macroscopic mixing in the radiative envelope (e.g., Deal et al 2016;Rogers & McElwaine 2017;Pedersen et al 2018;Mombarg et al 2020;Mathis et al 2021, Pedersen et al, submitted;Bugnet et al, submitted).…”
Section: Introductionmentioning
confidence: 99%